Controlled Reduction of Genomic Heterozygosity in an Industrial Yeast Strain Reveals Wide Cryptic Phenotypic Variation - Sampaio, Nadia M. V.; Watson, Ruth A.; Argueso, Juan Lucas (Frontiers in Genetics, 2019)
Abundant genomic heterozygosity can be found in wild strains of the budding yeast Saccharomyces cerevisiae isolated from industrial and clinical environments, but notably, the heterozygous alleles present in those strains are not evenly distributed across their genomes. Instead, heterozygosity is often clustered in discrete chromosomal regions, while other stretches are entirely homozygous. This patchwork configuration could be the net result of the interaction between two opposing forces: Genomic instability processes such as mitotic recombination that erode heterozygosis, and natural selection that may disfavor homozygous genotypes. We investigated this possibility in the bioethanol strain PE-2/JAY270, a natural hybrid whose genome is characterized by abundant, yet unevenly distributed, structural and nucleotide polymorphisms between most pairs of homologous chromosomes. This strain is widely adopted by distilleries for its ability to thrive under harsh biotic and abiotic stresses during fermentation. In this study, we set out to explore how changes in genomic heterozygosity can influence the traits of PE-2/JAY270. We manipulated the abundance and distribution of heterozygous alleles through two approaches: Inbreeding and targeted uniparental disomy (UPD). New unique combinations of homozygous alleles in each inbred strain resulted in wide phenotypic variation for at least two important complex traits: Heat stress tolerance and competitive growth kinetics. Genome-wide association analyses allowed the identification of broad genomic regions where genetic polymorphisms potentially impacted these two traits. Interestingly, there was no overlap between the loci associated with each trait. In addition, we adapted an approach to induce bidirectional UPD of three targeted pairs of chromosomes (IV, XIV, and XV), while heterozygosity was maintained elsewhere in the genome. In most cases UPD led to detectable phenotypic alterations, often in opposite directions between the two strains in each UPD pair. Our results showed that homozygosity of specific regions could uncover cryptic phenotypic diversity hiding within the PE-2/JAY270 genome, which if exposed, would likely be acted upon by natural selection. In addition, this study laid a foundation for an experimental pipeline that can be expanded and then applied to the identification of alleles of interest for industrial and clinical applications in this and other hybrid yeast strains.